The Effect of Profitability and Solvency on Stock Prices (Study on Property and Real Estate Companies Listed on the Indonesia Stock Exchange in 2019-2023) - Cahyaningsih Cahyaningsih; Fadhil Ade Permana; Brady Rikumahu (Universitas KH. Abdul Chalim Mojokerto, 2025)
Stock price is a key indicator that reflects a company's performance and serves as an essential factor for investors in making investment decisions. This study aims to examine the partial and simultaneous influence of profitability ratios and solvency ratios on stock prices of property and real estate sector companies listed on the Indonesia Stock Exchange (IDX) during the 2019-2023 period. Profitability ratio related to investment are measured using Return on Equity (ROE), while solvency ratio is measured using Debt to Equity Ratio (DER). The population in this study consists of all property and real estate sector companies listed on the IDX during the 2019-2023 period. The sample includes 31 companies over a five-year period, selected using the purposive sampling method. The analysis method applied is panel data regression. The results of this study are expected to provide valuable insights for investors, companies, and academics in understanding the factors affecting stock prices in the property and real estate sector.